Amalan dan prestasi dalam perolehan elektronik - Mohamad, Norhidayah (2006)
The practice and performance in electronic procurement (e-Procurement) is important due to its relation to the efficiency and effectiveness of the procurement process in an organization. However, organizations are reluctant to implement this system due to its intangible advantages to the businesses, hesitation on potential benefits and difficulties in using the e-Procurement software available in the market. Thus, the purpose of this research is to measure the level of in-house e-Procurement practices and performance, to identify the differences between e-Procurement practices and performance based on demographic factors and to elaborate the significant relationship between e-Procurement practices and performance. In addition, this research explores approaches that have been employed by Telekom Research and Development (TMR&D) Sdn. Bhd in developing e-Procurement system as well as solving the problems of such system. This study employs multimethod approach where distribution of survey questionnaires, interviews and observations were conducted accordingly over time. Findings of this research indicate that the levels of practices of e-Procurement in TMR&D is high at 55.5% and the level of performances of e-Procurement is moderate at 50.8%. The findings also support the research hypotheses, namely there is difference between education level and e-Procurement practices and performances, significant at 0.05 and there is significant relationship between e-Procurement practices and performance with r2=0.305. Even though there are few barriers in implementing such system, the level of barrier is low (2.31) and all these barriers have been overcome by the management in the early stage of the system’s development. In conclusion, developing an in house e-Procurement system is relatively cheaper and provide advantages that are almost similar to those offered by the existing system in the market. It can also be implemented at lower cost and allow organization to make changes to suit the system whenever neccessary.